Two-photon dissociation of H2O at 266 nm - Atkins, C; Briggs, R; Halpern, J; Hancock, G (1988)
The rotational energy distribution in the OH A 2Σ+ fragment of the two-photon dissociation of H2O at 266 nm has been measured. The form of the distribution is very similar to that following single-photon excitation at approximately the same energy, but the alignment of the photofragment is considerably less. Possible dissociation mechanisms for the two-photon excited molecules are discussed. © 1988.